Assessment of the potential industrial applications of commercial dried cassava products in Nigeria - Awoyale, W.; Abass, A.; Ndavi, M.; Maziya-Dixon, Busie; Sulyok, M. (Springer, 2017)
Variations in the functional and pasting properties of four groups of commercial dried cassava product in Nigeria were evaluated in this study, to explore their potential for use as industrial raw materials. In total, 692 products were analyzed using standard analytical methods. The functional and pasting properties of the samples were found to vary significantly (p < 0.05). Toasted cassava was found to have the highest water absorption capacity, at 467.42 %, and dried cassava the lowest, at 252.57 %. Conversely, dried cassava was found to have the highest peak and breakdown viscosities, and toasted cassava the lowest. A significant (p < 0.01) positive correlation was found to exist between dispersibility and the swelling power (r = −0.93) and solubility index (r = −0.84) of the cassava products. Meanwhile, the correlation between dispersibility and the peak (r = −0.75) and breakdown (r = −0.72) viscosities was positive and significant (p < 0.05). Therefore, the authors of this study conclude that user industries such as the food, paper, adhesives, textiles and plywood sectors might require information on the pre-processing of cassava-based feedstock, so as to predetermine the technical usability of such raw materials within their industrial processes.